2023
DOI: 10.1161/circinterventions.123.012991
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes With Percutaneous Debulking of Tricuspid Valve Endocarditis

Abstract: BACKGROUND: In patients with tricuspid valve infective endocarditis, percutaneous debulking is a treatment option. However, the outcomes of this approach are less well known. METHODS: We performed a retrospective analysis of all patients who underwent percutaneous vegetation debulking for tricuspid valve infective endocarditis from August 2020 to November 2022 at a large academic tertiary care public hospital. The primary efficacy outcome was procedural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Our study revealed an upward trend in PMA use in the management of RSIE which has been reflected in the literature, as there has been an increase in case series and registry data showing the expansion of the motives and applications of PMA in RSIE 12–17 . PMA has been predominately used in cases of RSIE as an adjunct to management where a response to appropriate antimicrobial therapy is not achieved or immediate valve surgery is not feasible.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Our study revealed an upward trend in PMA use in the management of RSIE which has been reflected in the literature, as there has been an increase in case series and registry data showing the expansion of the motives and applications of PMA in RSIE 12–17 . PMA has been predominately used in cases of RSIE as an adjunct to management where a response to appropriate antimicrobial therapy is not achieved or immediate valve surgery is not feasible.…”
Section: Discussionmentioning
confidence: 57%
“…This would then serve as a bridge to safer surgery with lower risk of infecting the prosthetic valve from injection drug use relapse 12 . Another common application is (5) elimination of the risk of recurrent SPE in patients despite antimicrobial therapy and at high operative risk, 12 This expansion in the application of PMA in multiple facets of management of RSIE may explain the increasing trends in its utilization as demonstrated in our investigation. These applications may also help in decision‐making for timing of intervention in PMA in RSIE.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Recent studies have suggested that percutaneous debulking of tricuspid valve infective endocarditis is feasible and safe. 2 Percutaneous debulking offers the advantage of delaying valve replacement in patients who are young and serves as a useful temporizing measure in patients with septic shock or, as observed in this instance, individuals at higher risk for cardiac surgery due to a recent cerebral vascular accident.…”
mentioning
confidence: 99%